1991
DOI: 10.1111/j.1445-5994.1991.tb01406.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomised trial of cyclosporin and methotrexate versus cyclosporin, methotrexate and prednisolone for prevention of graft‐versus‐host disease after HLA‐identical sibling marrow transplantation for haematological malignancy

Abstract: A prospective randomised trial was performed in patients given HLA-identical sibling bone marrow transplants for haematological malignancy comparing the combination of cyclosporin and methotrexate (CM) (n = 20) with the combination of cyclosporin, methotrexate and prednisolone (CMP) (n = 21) as prophylaxis for graft-versus-host disease (GVHD). There was no significant differences between the two arms for the incidence of acute GVHD grades I-IV, acute GVHD grades II-IV, chronic GVHD, interstitial pneumonitis, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…Several previous randomized studies in sibling bone marrow transplants, [6][7][8][9][10] although varying in duration of prednisolone prophylaxis and in some, comparing CSA/ MTX/Pred to CSA/Pred have generally found no reduction in acute GVHD incidence. In the unrelated donor bone marrow transplant setting, grade II-IV GVHD incidence did not significantly differ with the addition of prednisolone to CSA/MTX.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several previous randomized studies in sibling bone marrow transplants, [6][7][8][9][10] although varying in duration of prednisolone prophylaxis and in some, comparing CSA/ MTX/Pred to CSA/Pred have generally found no reduction in acute GVHD incidence. In the unrelated donor bone marrow transplant setting, grade II-IV GVHD incidence did not significantly differ with the addition of prednisolone to CSA/MTX.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Several investigators have reported the effects of combining prednisolone with CSA/ MTX in reducing GVHD after marrow allografts. [5][6][7][8][9][10][11][12][13] The schedule of prophylaxis has varied, with prednisolone commencing at days À7, 0, þ 14 or þ 15 and continuing until day þ 35, þ 110 or to day þ 180. A delay in onset of acute GVHD has been described in several series, 6,8,10 but in only one published report in sibling bone marrow recipients has a significant reduction in the overall incidence of grade II-IV acute GVHD been observed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators have studied the effect of the addition of PRED to the combination of CYA and MTX. [14][15][16][17] An increase in the incidence of acute and chronic GVHD was noted in one study, 14 with no difference in survival, and in two other studies, no advantage was noted in either survival or the incidence of GVHD. 15,16 In another study, an increase in the incidence of infection was noted with the addition of PRED, 18 but other studies did not confirm this observation.…”
mentioning
confidence: 99%
“…[14][15][16][17] An increase in the incidence of acute and chronic GVHD was noted in one study, 14 with no difference in survival, and in two other studies, no advantage was noted in either survival or the incidence of GVHD. 15,16 In another study, an increase in the incidence of infection was noted with the addition of PRED, 18 but other studies did not confirm this observation. 13,16 In a prospective study that compared CYA and PRED with CYA and MTX, Gondo et al 19 showed a lower incidence of chronic GVHD with the former combination, although other studies have noted a higher incidence of chronic GVHD with the CYA and PRED regimen.…”
mentioning
confidence: 99%